2021
DOI: 10.3390/pr9020338
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Characterization of Isotropic Pyrolytic Carbon Used for Mechanical Heart Valve Production

Abstract: Usage of pyrolytic carbon (PyC) to produce mechanical heart valves (MHVs) has led to heart valve replacement being a very successful procedure. Thus, the mechanical properties of employed materials for MHV production are fundamental to obtain the required characteristics of biocompatibility and wear resistance. In this study, two deposition methods of PyC were compared through a multiscale approach, performing three-point bending tests and nanoindentation tests. Adopted deposition processes produced materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The differences at these two scales can be attributed to the presence of voids, as observed in Figure 12 . Furthermore, other studies have revealed that the mechanical properties obtained at the microscale, which are strongly influenced by the microstructural features of the material under analysis, may differ from the mechanical properties at higher scale levels [ 65 , 66 ]. The testing area for nanoindentation, as shown in Figure 13 , was characterized by the absence of defects thanks to the polishing process required for nanoindentation tests.…”
Section: Resultsmentioning
confidence: 99%
“…The differences at these two scales can be attributed to the presence of voids, as observed in Figure 12 . Furthermore, other studies have revealed that the mechanical properties obtained at the microscale, which are strongly influenced by the microstructural features of the material under analysis, may differ from the mechanical properties at higher scale levels [ 65 , 66 ]. The testing area for nanoindentation, as shown in Figure 13 , was characterized by the absence of defects thanks to the polishing process required for nanoindentation tests.…”
Section: Resultsmentioning
confidence: 99%
“…The structural analysis of skeletal body elements and of biomechanical systems consisting of a bone element coupled to a prosthesis, an implant or a fracture synthesis device, can be performed both numerically and experimentally [18]. There are many examples of clinical problems, which have moved from a qualitative assessment to a quantitative evaluation thanks to the respective modelling or to the application of classical experimental methods of structural analysis to the evaluation of the efficacy of procedures or surgical techniques or to the evaluation of the mechanical characteristics of the materials used at different scales of investigation [76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92]. Moreover, the structural analysis of medical devices and biological tissues is strictly connected with the in-vivo behavior of their interaction [93,94].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the process conditions, pyrolytic carbon coatings can have isotropic, granular, lamellar, columnar, etc., structures. Although mainly used for heart valve protection [235], pyrolytic coatings have been applied for the replacement of small joints such as knuckles, wrist joints and proximal interphalangeal joints [236].…”
Section: Carbon-based Coatingsmentioning
confidence: 99%